2016
DOI: 10.5152/balkanmedj.2016.160180
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Speech Intelligibility Performance of Post Lingual Cochlear Implant Users at Different Signal-to-Noise Ratios Using the Turkish Matrix Test

Abstract: Background: Spoken word recognition and speech perception tests in quiet are being used as a routine in assessment of the benefit which children and adult cochlear implant users receive from their devices.Cochlear implant users generally demonstrate high level performances in these test materials as they are able to achieve high level speech perception ability in quiet situations. Although these test materials provide valuable information regarding Cochlear Implant (CI) users' performances in optimal listening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…In our study, the mean critical SNR was found to be −1.78 ± 4.21 dB in the TMT performed using adaptive noise. Polat et al [17] obtained an average SNR of −4.90 ± 3.47 dB, using the TMT with an adaptive method with Turkish CI recipients. Hey et al [19] found a mean of −2 dB SNR, using the German matrix test with an adaptive method with German CI recipients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the mean critical SNR was found to be −1.78 ± 4.21 dB in the TMT performed using adaptive noise. Polat et al [17] obtained an average SNR of −4.90 ± 3.47 dB, using the TMT with an adaptive method with Turkish CI recipients. Hey et al [19] found a mean of −2 dB SNR, using the German matrix test with an adaptive method with German CI recipients.…”
Section: Discussionmentioning
confidence: 99%
“…While speech sound signal was played from the speaker in the front (0 azimuth), noise was played from the one in the rear (180 azimuth) (Fig. 1) [17]. TMT consists of 20 sentences, and the test battery contains a total of 50 randomly presented word-base matrix sentences.…”
Section: Methodsmentioning
confidence: 99%
“…The scores were calculated as signal-to-noise threshold levels (dBSNR), where the listeners could correctly repeat more than 50% of the words. Speech stimuli were presented from 0°, and continuous 65 dBSPL bubble noise was presented from 180° azimuth ( 18 ). Before the test, all subjects performed a training session ( 17 ).…”
Section: Methodsmentioning
confidence: 99%